Identification and Validation of Key Genes of Differential Correlations in Gastric Cancer - Chen, Tingna; He, Qiuming; Xiang, Zhenxian; Dou, Rongzhang; Xiong, Bin (Frontiers in Cell and Developmental Biology, 2022)
Background: Gastric cancer (GC) is an aggressive cancer with poor prognosis. Previously bulk transcriptome analysis was utilized to identify key genes correlated with the development, progression and prognosis of GC. However, due to the complexity of the genetic mutations, there is still an urgent need to recognize core genes in the regulatory network of GC. Methods: Gene expression profiles (GSE66229) were retrieved from GEO database. Weighted correlation network analysis (WGCNA) was employed to identified gene modules mostly correlated with GC carcinogenesis. R package ‘DiffCorr’ was applied to identify differentially correlated gene pairs in tumor and normal tissues. Cytoscape was adopted to construct and visualize the gene regulatory network. Results: A total of 15 modules were detected in WGCNA analysis, among which 3 modules were significantly correlated with GC. Then genes in these modules were analyzed separately by ‘DiffCorr’. Multiple differentially correlated gene pairs were recognized and the network was visualized by the software Cytoscape. Moreover, GEMIN5 and PFDN2, which were rarely discussed in GC, were identified as key genes in the regulatory network and the differential expression was validated by real-time qPCR, WB and IHT in cell lines and GC patient tissues. Conclusions: Our research has shed light on the carcinogenesis mechanism by revealing differentially correlated gene pairs during transition from normal to tumor. We believe the application of this network-based algorithm holds great potential in inferring relationships and detecting candidate biomarkers.